The association between toxic pesticide environmental exposure and Alzheimer's disease: A scientometric and visualization analysis. (January 2021) - Li, Yanan; Fang, Ruying; Liu, Zehua; Jiang, Luping; Zhang, Jingdong; Li, Honghu; Liu, Chaoyang; Li, Fei
Abstract: Alzheimer's disease (AD) is one of the most common neurodegenerative diseases. The association between environmental factors (e.g., pesticide) and AD has attracted considerable attention. However, no systematic analysis has been performed and make it difficult to provide deeper insights of AD correlated with pesticide exposure. Hence, this study utilized a bibliometric and visual approach that included map collaborations, co-citations, and keywords, to identifying the knowledge structure, hot topics and the research trends based on 372 publications from the Web of Science Core Collection and PubMed databases. The results showed that 116 institutions from 52 countries published articles in this field. The United States and Israel played a leading role with numerous publications in related journals, as well as prolific institutions and authors, respectively. Three hot topics in pesticide-induced AD were recognized based on co-occurrence keywords detection, including acetylcholinesterase (AChE) inhibitor, oxidative stress, and AChE. Moreover, analysis of keywords burst suggests that some potential molecular mechanisms and therapy targets of pesticide-induced AD, especially for mitochondrial dysfunction and monoamine oxidase-B (MAO-B) that catalyzes the oxidative deamination and causes oxidative stress, are emerging trends. In addition, the study of various pesticides and the assessment method of pesticide exposure will step forward as well. To the best of our knowledge, this study is the first to specifically visualize the relationship between AD and pesticide exposure and to predict potential future research directions. Graphical abstract: Image 1 Highlights: This novel study performed scientometric analysis of research on the association between pesticide exposure and AD. The US and Israel played a leading role in the research field of pesticide-induced AD. Acetylcholinesterase (AChE) inhibitor, oxidative stress, and AChE were recognized as three hot topics. Investigating the molecular mechanisms of pesticide-induced AD has raised concern and become a common trend.